2006
DOI: 10.1007/s00418-006-0160-y
|View full text |Cite
|
Sign up to set email alerts
|

Location of cell cycle regulators cyclin B1, cyclin A, PCNA, Ki67 and cell cycle inhibitors p21, p27 and p57 in human first trimester placenta and deciduas

Abstract: Although placental development and implantation depend on the coordination of trophoblast proliferation, differentiation and invasion, little is known about the cell cycle regulators that govern the control of these events. The hypothesis that the coordinated expression of cell cycle progression and inhibition factors will determine whether cytotrophoblasts proliferate or undergo cell cycle arrest or cell cycle exit allowing subsequent differentiation was tested. The cell cycle promotors cyclin A, cyclin B1, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 33 publications
5
45
0
Order By: Relevance
“…3 Until now, little has been known about the interplay of cell cycle regulators, and it has been impossible to determine whether trophoblast cells proliferate or exit from the cell cycle to allow further differentiation. 35,36 The results of previous experiments using the choriocarcinoma cell line Jeg3 suggested that CCN3 causes an imbalance between the proliferation and migration of human trophoblast cells. 13,14,22 In the present study we found that both glycosylation forms of CCN1 and CCN3 proteins reduce the numbers of benign SGHPL-5 trophoblast cells, whereas in Jeg3 cells only CCN3 seems to regulate proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…3 Until now, little has been known about the interplay of cell cycle regulators, and it has been impossible to determine whether trophoblast cells proliferate or exit from the cell cycle to allow further differentiation. 35,36 The results of previous experiments using the choriocarcinoma cell line Jeg3 suggested that CCN3 causes an imbalance between the proliferation and migration of human trophoblast cells. 13,14,22 In the present study we found that both glycosylation forms of CCN1 and CCN3 proteins reduce the numbers of benign SGHPL-5 trophoblast cells, whereas in Jeg3 cells only CCN3 seems to regulate proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The results may also challenge the concept of differential mitotic activity in the proximal and distal parts of the first trimester cytotrophoblast cell column, but more functional studies are clearly needed. The presence of p27 and p57 in EVT cells, which invade the deciduas deeply, may account for the loss of mitogenic potential of these cells [84].…”
Section: The Effects Of Glucocorticoids On Placental Cell Cyclementioning
confidence: 99%
“…Regulation of cell polyploidization of the human EVT is not understood completely, although some data suggest similarity and specificity as compared to the rodent trophoblast. Thus, "mitotic" cyclins A and B1 as well as Ki-67 and PCNA were immunolocalized in proximal and distal EVT as well as in the EVT that invaded the upper decidual segments (Korgun et al, 2006). Cell cycle inhibitors p27 and p57 were expressed in all extravillous trophoblast cells (EVT), but p21 was not.…”
Section: Genome Multiplication Of the Extravillous Trophoblast Cells mentioning
confidence: 98%
“…Meantime, a strong expression of p57 may be a feature of the endoreduplication cycle, because p57, being the S-phase inhibitor, proves oscillatory expression in the course of mouse giant trophoblast cell endoreduplication (Hattori et al, 2000;Hu, Cross, 2010). Mitotic cyclin B1 (as judged from the photo, Korgun et al, 2006) also shows downregulation in the invasive pathway. The immunolabelled cells may be found in the CC, but not inside the decidualized endometrium.…”
Section: Genome Multiplication Of the Extravillous Trophoblast Cells mentioning
confidence: 99%